Предмет: Алгебра, автор: Кипитмозг

1)Упростить выражение
a) cos^2*(pi+t)+cos^2*(pi-t)
б) sin*(pi/2-t)*tg*(-t)
         cos(pi/2+t)
2)Решите уравнение
cos*(2pi-t)-sin*(3pi/2+t)=1

Ответы

Автор ответа: Аноним
0
displaystyle a),,, cos^2(pi + t)+cos^2(pi -t)=cos^2t+cos^2t=2cos^2t\ \ b),,,  frac{sin( frac{pi}{2} -t)cdot tg(-t)}{cos(frac{pi}{2}+t)} = frac{cos tcdot(-tg t)}{-sin t} = frac{sin t}{sin t}=1\ \ 2),,, cos(2 pi -t)-sin(frac{3pi}{2}+t)=1\ \ cos t + cos t = 1\ \ 2cos t = 1\ \ cos t = 0.5\ \ x=pm frac{pi}{3} +2 pi n,n in Z
Похожие вопросы
Предмет: Алгебра, автор: tairtulenov8
Предмет: Английский язык, автор: myrzasevazanerke